Individual- and Community-Level Risk Factors Associated with Childhood Diarrhea in Ethiopia: A Multilevel Analysis of 2016 Ethiopia Demographic and Health Survey - Setegn Muche Fenta; Teshager Zerihun Nigussie (International Journal of Pediatrics)
Background. Diarrhea is the second cause of child deaths globally. According to World Health Organization reports, in each year, it kills more than 525,000 children under 5 years. More than half of these deaths occur in five countries including Ethiopia. This study is aimed at identifying both individual- and community-level risk factors of childhood diarrhea in Ethiopia. Methods. Ethiopian demography and health survey of 2016 data were used for the analysis. A total of 10,641 children aged 0–59 months were included in the analysis. A multilevel mixed-effects logistic regression model was used to identify both individual- and community-level risk factors associated with childhood diarrhea. Result. The incidence of childhood diarrhea was 12% (95% CI: 11.39, 12.63). The random-effects model revealed that 67% of the variability of childhood diarrhea was explained by individual- and community-level factors. From the individual-level factors, children aged 36–59 months (AOR=3.166; 95% CI: 2.569, 3.900), twin child (AOR=1.871; 95% CI: 1.390, 2.527), birth order 5 and above (AOR=2.210, 95% CI: 1.721, 2.839), not received any vaccination (AOR=1.197; 95% CI: 1.190, 1.527), smaller size of child at birth (AOR=1.303; 95% CI: 1.130, 1.504), and never breastfed children (AOR=2.91; 95% CI: 2.380, 3.567) associated with the higher incidence of childhood diarrhea. From the community-level factors, living in a rural area (AOR=1.505; 95% CI: 1.233, 1.836)), unprotected source of drinking water (AOR=1.289; 95% CI: 1.060, 1.567), and availability of unimproved latrine facilities (OR: 1.289; 95% CI: 1.239, 1.759) associated with the higher incidence of childhood diarrhea. Besides, children who live in Afar, Amhara, Benishangul-Gumuz, Gambella, SNNPR, and Dire Dawa regions had higher incidence of childhood diarrhea. Conclusion. The incidence of childhood diarrhea was different from cluster to cluster in Ethiopia. Therefore, integrated child health intervention programs including provisions of toilet facility, access to a clean source of drinking water, educate parents about the importance of breastfeeding, and vaccination have to be strongly implemented in order to reduce the high incidence of childhood diarrhea among children in Ethiopia.